SUITABILITY MAPPING FOR OPTIMAL LANDFILL SITE IN COASTAL MOUNTAIN MUNICIPALITIES. CASE STUDY: COLLO MASSIF (NORTHEASTERN ALGERIA) - Siham Agaguenia,; Mahrez Boulabeiz,; Gihen Rym Abdaoui,; Fatima Dahdouh, (International Journal of Innovative Technologies in Social Science, 2024)
The management of Municipal Solid Waste (MSW) in coastal mountainous regions displays a significant challenge to sustainable development in Algeria, particularly in its environmental dimension. Local stakeholders face substantial difficulties in identifying appropriate sites for solid waste disposal in this area due to the fragility and complexity of their ecological systems and their potential to amplify the impacts of waste disposal. This affects directly the quality of life, sustainability of natural resources, and threatens the scenic beauty of this tourist destination. Therefore, developing a mechanism based on scientific knowledge to facilitate decision-making processes in these regions is imperative. This paper aims to underscore the importance of employing Cartographic Suitability Mapping for Optimal Landfill Site Selection in coastal mountainous regions as an effective tool to ensure precise results, focusing on the study case of Collo, Skikda state, Algeria. The results show four categories of land suitability: constraint (5.22-7.76) , unsuitable (3.25-4.26), and suitable area (1.21-3.24), with four candidate areas identified as the most suitable for landfill establishment. It is recommended that future studies incorporate social and economic dimensions to further enhance decision-making processes in this regard.